Reduction of peripersonal comfort space correlate with eating disorder symptoms in young adolescents: a network analysis approach - Pereira Da Silva, Beatriz; Escelsior, Andrea; Biggio, Monica; Zizzi, Alessio; Belvederi Murri, Martino; Guglielmo, Riccardo; Inuggi, Alberto; Delfante, Federico; Marenco, Giacomo; Amore, Mario; Serafini, Gianluca (Frontiers in Psychology, 2024)
Background: Peripersonal Space (PS) is represented as the immediate area surrounding an individual. The extent of PS changes in relation to several factors, including emotional states, type of relationship or psychopathology. Attachment anxiety has an impact on the social adaptability of peripersonal space and anxiety and fear are associated with an expansion of peripersonal space, possibly serving as a mechanism of self-protection. Peripersonal space appears to be intricately linked to various psychiatric conditions like anxiety disorders and converging evidence suggests that social maladjustment may predict or exacerbate eating disorder symptoms expression. Methods: Fifty-eight healthy adolescents (38F, 20M) performed a comfort distance estimation task to assess peripersonal space. The Adolescent/Adult Sensory Profile (AASP) was used to assess sensory profiles and the SAFA protocol to investigate psychopathological aspects. Data was analysed using Network Analysis, estimating a Gaussian Graphical Models with a Bayesian approach. Results: We found that the task related to comfort estimation distance demonstrated a correlation with the visual scale of the Adolescent/Adult Sensory Profile (AASP). Additionally, a correlation was observed with the Eating Disorder scale of the SAFA protocol. The touch scale also was negatively correlated with Eating disorder symptoms but not with the comfort estimation task. Conclusion: Our results demonstrate a relation between peripersonal space and eating disorder symptoms in healthy adolescents in line with previous findings in adults with eating disorders diagnosis. These findings suggest that socio-emotional difficulties may be possible precursors or reinforce for the development of an eating disorder symptoms.